Regulator of G-Protein Signaling 5 Reduces HeyA8 Ovarian Cancer Cell Proliferation and Extends Survival in a Murine Tumor Model - Molly K. Altman; Duy T. Nguyen; Santosh B. Patel; Jada M. Fambrough; Aaron M. Beedle; William J. Hardman; Mandi M. Murph (Biochemistry Research International)
The regulator of G-protein signaling 5 (RGS5) belongs to a family of GTPase activators that terminate signaling cascades initiated by extracellular mediators and G-protein-coupled receptors. RGS5 has an interesting dual biological role. One functional RGS5 role is as a pericyte biomarker influencing the switch to angiogenesis during malignant progression. Its other functional role is to promote apoptosis in hypoxic environments. We set out to clarify the extent to which RGS5 expression regulates tumor progression—whether it plays a pathogenic or protective role in ovarian tumor biology. We thus constructed an inducible gene expression system to achieve RGS5 expression in HeyA8-MDR ovarian cancer cells. Through this we observed that inducible RGS5 expression significantly reduces in vitro BrdU-positive HeyA8-MDR cells, although this did not correlate with a reduction in tumor volume observed using an in vivo mouse model of ovarian cancer. Interestingly, mice bearing RGS5-expressing tumors demonstrated an increase in survival compared with controls, which might be attributed to the vast regions of necrosis observed by pathological examination. Additionally, mice bearing RGS5-expressing tumors were less likely to have ulcerated tumors. Taken together, this data supports the idea that temporal expression and stabilization of RGS5 could be a valuable tactic within the context of a multicomponent approach for modulating tumor progression.